2016
DOI: 10.4103/0970-4388.180446
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of child behavior in dental operatory in relation to sociodemographic factors, general anxiety, body mass index and role of multi media distraction

Abstract: Among sociodemographic factors, increasing age is directly related to child's positive behavior, whereas other factors such as gender and socioeconomic status (SES) are not significantly related. General anxiety significantly affects the child's behavior. BMI of the child is not related to child's behavior in dental operatory. Multimedia was not found to be significantly affecting the behavior of the child in dental operatory. Interpretations and Conclusion: The principle conclusion of this study is that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
3
11
0
2
Order By: Relevance
“…To the best of our knowledge, this is the first Englishlanguage study addressing this issue. Moreover, previous studies on parental involvement in pediatric dentistry have been largely focused on assessing the effect of variables like parental presence during operation (34), parents' dental fear and anxiety (15,24,25), and child-rearing practice on child's behavior (2,22,23,(28)(29)(30). In the present study, the behavior was found to be significantly better in the intervention group than in the control group.…”
Section: )supporting
confidence: 42%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first Englishlanguage study addressing this issue. Moreover, previous studies on parental involvement in pediatric dentistry have been largely focused on assessing the effect of variables like parental presence during operation (34), parents' dental fear and anxiety (15,24,25), and child-rearing practice on child's behavior (2,22,23,(28)(29)(30). In the present study, the behavior was found to be significantly better in the intervention group than in the control group.…”
Section: )supporting
confidence: 42%
“…Overall, the child's dental behavior plays a key role in providing adequate treatment (15). Different surveys have investigated the association between the child's dental behavior and variables like age, gender, maturity, family background (16,17), emotional condition (2), unfavorable medical or dental history (15,18,19), personality traits (2,15,16), temperament (20-23), parents' dental fear and anxiety (15,16,19,(24)(25)(26), parental attitudes and perceptions (27), and parental rearing style (2,22,23,(28)(29)(30). The family atmosphere, where the child has been raised, also seems to affect the multidimensionality of his/her personality (2, 15, Definitely negative Pronounced refusal of the dental procedure, crying forcefully, being fearful, or any other overt evidence of extreme negativism.…”
Section: Discussionmentioning
confidence: 99%
“…Sayed[20] concluded that projecting the visual output of the dental procedures is effective in distracting the child patient during the procedure and subsequently reducing dental anxiety. In contrast, Mishra[21] stated that the multimedia was not found to be significantly affecting the behavior of the child in dental operatory.…”
Section: Introductionmentioning
confidence: 99%
“…They found that SES was not correlated with DA. On the other hand, Mishra et al in 2016 (26) found that patients with high SES had the highest incidence of negative behavior. In addition, Jamali Z et al in 2017 (12) found that children with DA belonged to high and middle SES.…”
Section: Discussionmentioning
confidence: 99%